CircGLIS3 Promotes High-Grade Glioma Invasion via Modulating Ezrin Phosphorylation - Li, Yan; Chen, Jiansheng; Chen, Zetao; Xu, Xiangdong; Weng, Jun; Zhang, Yuxuan; Mo, Yunzhao; Liu, Yang; Wang, Jihui; Ke, Yiquan (Frontiers in Cell and Developmental Biology, 2021)
High-grade glioma is highly invasive and malignant, resistant to combined therapies and easy to relapse. A better understanding of circRNA biological function in high-grade glioma might contribute to the therapeutic efficacy. Here, a circRNA merely up-regulated in high-grade glioma, circGLIS3 (hsa_circ_0002874, originating from exon 2 of GLIS3), was validated by microarray and qRT-PCR. The role of circGLIS3 in glioma was assessed by functional experiments both in vitro and in vivo. Fluorescence in situ hybridization, RNA pull-down, RNA immunoprecipitation and immunohistochemical staining were performed for mechanistic study. Co-cultured brain endothelial cells with glioma explored the role of exosome-derived circGLIS3 in glioma microenvironment. We found up-regulation of circGLIS3 promoted glioma cell migration and invasion, and showed aggressive characteristics in tumor-bearing mice. Mechanistically, we found circGLIS3 could promote Ezrin T567 phosphorylation level. Moreover, circGLIS3 could be excreted by glioma through exosomes and induced endothelial cells angiogenesis. Our findings indicate that circGLIS3 is up-regulated in high-grade glioma and contributes to the invasion and angiogenesis of glioma via modulating Ezrin T567 phosphorylation.